Iatrogenic ureteral injuries and their prevention in colorectal surgery: results from a nationwide survey. (30th January 2019) - Douissard, J.; Meyer, J.; Ris, F.; Liot, E.; Morel, P.; Buchs, N. C.
Abstract: Aim: Iatrogenic ureteral injury (IUI) occurs rarely during colorectal surgery but is associated with significant mortality, morbidity and medicolegal issues. Few cases are reported, and recommendations regarding prevention are lacking. The aim of this study is to describe the current state of practice regarding IUI and its prevention among general surgeons in Switzerland. Method: All Swiss general surgeons who are members of either the Swiss Association of Laparoscopic and Thoracoscopic Surgery or the Swiss Surgical Society were invited to participate in an anonymous online survey. Demographics, surgical practice, rate of IUI and methods used to prevent IUI were investigated. Results: All participants were board‐certified general surgeons, 63.4% were certified visceral surgeons and 17.9% were certified colorectal surgeons. The mean level of experience in colorectal surgery was 15.6 ± 9.2 years. Formal ureter identification was considered mandatory during sigmoid or rectal surgery by 83.7% of participants, and 31.7% considered identification of the right ureter during right colectomy to be mandatory. In total, 61.8% of the participants and 78.4% of surgeons with more than 20 years of experience had encountered at least one IUI. Prophylactic ureteral stenting was considered useful in complex procedures by 93.5% of participants, and 56.9% had used stents at least once in the past 12 months. Noninvasive techniques for identifying ureters would be considered in regular daily practice by 54.5% of the participants. Conclusion: Most general surgeons experience IUI. Ureter identification is widely integrated in colorectal procedures. Prophylactic stenting is widely used for difficult cases. Noninvasive methods to improve ureter identification are now needed.